Female sex as a risk factor for ischaemic stroke varies with age in patients with atrial fibrillation. Issue 7 (26th September 2019) - Wu, Victor Chien-Chia; Wu, Michael; Aboyans, Victor; Chang, Shang-Hung; Chen, Shao-Wei; Chen, Mien-Cheng; Wang, Chun-Li; Hsieh, I-Chang; Chu, Pao-Hsien; Lin, Yu-Shen
Abstract : Objectives: Female sex is an inconsistent ischaemic stroke risk factor in patients with atrial fibrillation (AF). We hypothesised that the ischaemic stroke risk varies with age among women compared with men. Methods: We retrieved the patients with newly diagnosed AF during 2001–2013 from Taiwan's National Health Insurance Research Database. Patients with missing information, age <20 years, history of valvular heart disease and surgery, rheumatic heart disease, hyperthyroidism or anticoagulation and/or antiplatelet use were excluded. Propensity score matching (PSM) included patient comorbidities, medications and index date stratified by age and sex groups. Primary outcome was defined as ischaemic stroke at follow-up. Results: After exclusion criteria, 87 369 men and 71 853 women remained for analysis (aged 73.1±14.4 years). After 1:1 PSM, we included 59 583 men (aged 73.5±13.7 years) and 59 583 women (aged 73.4±13.8 years) for analysis. We also stratified patients by age. The ischaemic stroke risk varied with age in women compared with men: lower in the ≤55 years (subdistribution HR (SHR)=0.75, 95% CI 0.62 to 0.90) and 56–65 years (SHR=0.87, 95% CI 0.78 to 0.98) groups, neutral in the 66–75 years group (SHR=1.01, 95% CI 0.94 to 1.08) and adverse in the >75 years group (SHR=1.14, 95% CI 1.09 to 1.19). Conclusions: The female/male ischaemic stroke risk ratio varied with age. Only women aged >75 years had a higher risk, whereas women aged <65 years had a lower risk compared with men. These findings challenge the 'sex category' component of the CHA2 DS2 -VASc score, used to make decision regarding anticoagulation treatment in AF patients.